THE ROLE OF CLASSICAL MUSIC ART IN HIGHER MUSICAL AND PEDAGOGICAL EDUCATION - Islom Akhtamov (Zeta Repository, 2023)
This article examines the role of classical musical art in the process of musical and pedagogical education, the high educational possibilities of such samples of professional musical art as makom, dastan, classical melody and ashula, katta ashula in educating young people in the spirit of high human feelings